2004
DOI: 10.1007/s10856-004-5739-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evaluation of bioartificial hydrogels as potential tissue engineering scaffolds

Abstract: Poly(vinyl alcohol) hydrogels prepared by freeze-thawing procedure represent synthetic systems widely investigated as non-biodegradable scaffolds for tissue regeneration. In order to improve the biocompatibility properties of pure poly(vinyl alcohol) (PVA) hydrogels, blends of PVA with different biological macromolecules, such hyaluronic acid, dextran, and gelatin were prepared and used to produce "bioartificial hydrogels". The porosity characteristics of these hydrogels were investigated by scanning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 1 publication
1
52
0
1
Order By: Relevance
“…Pore sizes were in the range of 100-400 μm, an optimal size for tissue engineering applications [41]. This outcome contrasts with the non-porous structure of plain SF scaffolds and with the small pores observed in polyvinylalcohol/HA scaffolds as prepared by Cascone et al [39].…”
Section: Scaffold Design: Composition and Microstructurementioning
confidence: 88%
See 1 more Smart Citation
“…Pore sizes were in the range of 100-400 μm, an optimal size for tissue engineering applications [41]. This outcome contrasts with the non-porous structure of plain SF scaffolds and with the small pores observed in polyvinylalcohol/HA scaffolds as prepared by Cascone et al [39].…”
Section: Scaffold Design: Composition and Microstructurementioning
confidence: 88%
“…This approach was based on the work of Cascone et al who showed that porous matrices (pore size 10-50 μm) may be prepared just by freeze-drying a structural polymer (polyvinylalcohol) with a blender (HA or gelatine) [39]. An interesting feature of this method is that it avoids the use of conventional porogens and the associated harsh manufacturing protocols that are typically required to extract them, such as leaching with aqueous or organic media [8,40].…”
Section: Scaffold Design: Composition and Microstructurementioning
confidence: 99%
“…(16)(17)(18) Blends of poly(vinyl alcohol) with different biological macromolecules, such as hyaluronic acid, dextran and gelatin were applied to produce bioartificial hydrogels functioning as potential tissue engineering scaffolds. (19) In the present work, a cryogenic treatment is applied on gelatin for biomedical use. Gelatin has been widely applied in medicine as a wound dressing (22) and as an adhesive and absorbent pad for surgical use.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of their use are engineering of tissue phantoms, designing extracellular matrices for tissue regeneration, and developing efficient drug delivery systems [1][2][3][4][5]. Understanding their structural and dynamical properties is therefore necessary, especially with the growing demand for hydrogels tailored for specific applications.…”
Section: Introductionmentioning
confidence: 99%